Contemporary Islamic values revisited. - Salleh, Shukri (2015)
This paper attempts to revisit the state of contemporary Islamic values. especially in their present usage. The contemporary Islamic values seem to have been molded by the needs and trends of the changing world, while their usage seems to be meant more of worldly pursuit rather the pursuit of the world Hereafter, let alone the balance between the two.